Engineered Multivalent Sensors to Detect Coexisting Histone Modifications in Living Stem Cells. Issue 1 (18th January 2018) - Delachat, Aurore M.-F.; Guidotti, Nora; Bachmann, Andreas L.; Meireles-Filho, Antonio C.A.; Pick, Horst; Lechner, Carolin C.; Deluz, Cédric; Deplancke, Bart; Suter, David M.; Fierz, Beat
Summary: The regulation of fundamental processes such as gene expression or cell differentiation involves chromatin states, demarcated by combinatorial histone post-translational modification (PTM) patterns. The subnuclear organization and dynamics of chromatin states is not well understood, as tools for their detection and modulation in live cells are lacking. Here, we report the development of genetically encoded chromatin-sensing multivalent probes, cMAPs, selective for bivalent chromatin, a PTM pattern associated with pluripotency in embryonic stem cells (ESCs). cMAPs were engineered from a set of PTM-binding (reader) proteins and optimized using synthetic nucleosomes carrying defined PTMs. Applied in live ESCs, cMAPs formed discrete subnuclear foci, revealing the organization of bivalent chromatin into local clusters. Moreover, cMAPs enabled direct monitoring of the loss of bivalency upon treatment with small-molecule epigenetic modulators. cMAPs thus provide a versatile platform to monitor chromatin state dynamics in live cells. Graphical Abstract: Highlights: Chromatin-sensing multivalent probes (cMAPs) enable imaging of histone PTM patterns cMAPs were designed to recognize bivalent chromatin in living stem cells Subnuclear localization of cMAPs demonstrates that bivalent domains form clusters cMAPs reveal how small-molecule epigenetic modulators affect bivalent chromatin Abstract : Delachat et al. developed cMAPs as genetically encoded, multivalent probes selective for bivalent chromatin, a histone modification pattern in stem cells. Engineered from natural reader domains, cMAPs enable visualization of the bivalent state in living cells, demonstrating that bivalent chromatin is organized in subnuclear clusters.